2004
DOI: 10.1093/treephys/24.7.753
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in ecosystem structure and function and effects on water and carbon exchange in ponderosa pine

Abstract: As forests age, their structure and productivity change, yet in some cases, annual rates of water loss remain unchanged. To identify mechanisms that might explain such observations, and to determine if widely different age classes of forests differ functionally, we examined young (Y, approximately 25 years), mature (M, approximately 90 years) and old (O, approximately 250 years) ponderosa pine (Pinus ponderosa Dougl. ex P. Laws.) stands growing in a drought-prone region of central Oregon. Although the stands d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 27 publications
9
92
1
1
Order By: Relevance
“…), assuming that trees had reached equilibrium with the soil during the night, and that ΚPD represents an estimate of soil water potential [45]. The following equation was used:…”
Section: Whole-tree Leaf-specific Hydraulic Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…), assuming that trees had reached equilibrium with the soil during the night, and that ΚPD represents an estimate of soil water potential [45]. The following equation was used:…”
Section: Whole-tree Leaf-specific Hydraulic Conductancementioning
confidence: 99%
“…Compared to P. sylvestris, Q. ilex showed lower ΚPD and a steeper decline of this variable with decreasing SWC. If we assume that ΚPD is in equilibrium with SWC around roots [45], these results would suggest that P. sylvestris roots have access to wetter soil pockets. This result contradicts the evidence showing that Q. ilex trees tend to be particularly deep rooted and reach deeper (and presumably wetter) soil layers than pines [55]; and authors' personal observations in the study area], as also shown in other pine-oak ecosystems, where higher ΚPD values were found for oak trees compared to co-occurring pines [56].…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexmentioning
confidence: 99%
“…In addition, WS77 had twice as many pine seedlings and more pine saplings per hectare than WS80. Young pines have much higher water use rates than mature pines (Irvine et al, 2004) due to both leaf area and high transpiration per unit leaf area (Delzon and Loustau, 2005). Song et al (2012) analyzed the recovery of South Carolina forests after Hugofour of their 1 ha plots are located in WS80 and were measured from 1994 through 2012.…”
Section: A D Jayakaran Et Al: Hurricane Impacts On a Pair Of Coastmentioning
confidence: 99%
“…As trees age, their hydraulic properties change, and at the same time, the amount of radiation intercepted by the canopy varies substantially [17]. With the increased size of the tree, water and nutrients must be transported over increasing distances between the root and the apex [7].…”
Section: Discussionmentioning
confidence: 99%